2008
DOI: 10.1007/s00442-008-1229-1
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of nitrogen increases with precipitation across a major grassland gradient in the Central Great Plains of North America

Abstract: Regional analyses and biogeochemical models predict that ecosystem N pools and N cycling rates must increase from the semi-arid shortgrass steppe to the sub-humid tallgrass prairie of the Central Great Plains, yet few field data exist to evaluate these predictions. In this paper, we measured rates of net N mineralization, N in above- and belowground primary production, total soil organic matter N pools, soil inorganic N pools and capture in resin bags, decomposition rates, foliar (15)N, and N use efficiency (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
75
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 64 publications
(66 reference statements)
12
75
2
Order By: Relevance
“…First, highly pulsed rainfall events typically found in drylands 30,31 may decouple plant N uptake with soil microbial N transformation in areas with AIo0.32. When the threshold AI ¼ 0.32 was passed, these two processes are probably coupled, resulting in higher N retention efficiency (that is, higher f plant ) with increasing AI.…”
Section: Discussionmentioning
confidence: 99%
“…First, highly pulsed rainfall events typically found in drylands 30,31 may decouple plant N uptake with soil microbial N transformation in areas with AIo0.32. When the threshold AI ¼ 0.32 was passed, these two processes are probably coupled, resulting in higher N retention efficiency (that is, higher f plant ) with increasing AI.…”
Section: Discussionmentioning
confidence: 99%
“…At the local scale, some studies report that mineral N concentration decreases with increasing water availability (Fisher et al 1987) and some report the opposite pattern (Whitford et al 1995). Other studies show that net N mineralization does not differ between dry or wet soils (Schimel and Parton 1986, Reynolds et al 1999, Yahdjian et al 2006, or across precipitation gradients in the Great Plains (McCulley et al 2009). A metaanalysis of aboveground net primary production (ANPP) responses to N fertilization across arid to subhumid ecosystems showed that the importance of N limitation increases with annual precipitation from arid to subhumid regions (Yahdjian et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Drier sites along precipitation gradients have shown a more ''open'' N cycle than sites receiving higher precipitation (Handley et al 1999), which means that the loss relative to N cycled between plants and soil is larger than in wetter sites. Thus, the indirect effect of precipitation through changes in the openness of the N cycle has significant impacts on ecosystem functioning, and has been proposed to maintain water and N co-limitation in semi-arid ecosystems (McCulley et al 2009). Within this context, we were interested in looking at the degree of synchrony between N availability and demand and how this relationship changes in dry and wet years in a desert grassland.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation drives maximum C input to the soil and varies across ecosystem biomes, primarily with moisture gradients (Del Grosso et al 2008;Jobbagy and Jackson 2000). Consequently, SOC and SON stocks are also highly related to temperature and precipitation gradients (Jenny 1941;Burke et al 1989;McCulley et al 2009). Temperature and moisture serve as controls to soil organic matter (SOM) decomposition and CO 2 respiration (Jobbagy and Jackson 2000;Conant et al 2004), driving both global and regional patterns of SOC.…”
mentioning
confidence: 99%